2022
DOI: 10.3847/2041-8213/ac4015
|View full text |Cite
|
Sign up to set email alerts
|

Parker Solar Probe Evidence for the Absence of Whistlers Close to the Sun to Scatter Strahl and to Regulate Heat Flux

Abstract: Using the Parker Solar Probe FIELDS bandpass-filter data and SWEAP electron data from Encounters 1 through 9, we show statistical properties of narrowband whistlers from ∼16 R s to ∼130 R s, and compare wave occurrence to electron properties including beta, temperature anisotropy, and heat flux. Whistlers are very rarely observed inside ∼28 R s (∼0.13 au). Outside 28 R s, they occur within a narrow range of parallel electron beta from ∼1 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 56 publications
12
38
1
Order By: Relevance
“…This is in itself an important result, as many theories of halo generation presuppose some local wave mechanism, that for example could scatter the strahl population into the halo. However, the absence of halo and/or strahl diffusion is consistent with the recent measurements of Cattell et al (2022); Jeong et al (2022a) which respectively show that whistler and FM/W waves do not scatter the strahl near the Sun. Our results do not preclude the occasional action of instabilities that derive their free energy from the halo particles, which have been observed e.g., at 1 AU (Tong et al 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in itself an important result, as many theories of halo generation presuppose some local wave mechanism, that for example could scatter the strahl population into the halo. However, the absence of halo and/or strahl diffusion is consistent with the recent measurements of Cattell et al (2022); Jeong et al (2022a) which respectively show that whistler and FM/W waves do not scatter the strahl near the Sun. Our results do not preclude the occasional action of instabilities that derive their free energy from the halo particles, which have been observed e.g., at 1 AU (Tong et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Observations have struggled to confirm these theories. Notably, whistlers are practically absent (occurrence rate <0.1%) during PSP perihelion passes (Cattell et al 2022). Additionally, the eVDFs sampled by Helios and PSP are stable with respect to the oblique FM/W mode (Jeong et al 2022a).…”
Section: Introductionmentioning
confidence: 97%
“…A kinetic expansion model for the solar-wind electrons suggests, however, that the oblique FM/W instability is unlikely to occur regularly and scatter the electron strahl at heliocentric distances below 20r s (Jeong et al 2022). Moreover, whistler waves are barely detected by PSP within 28r s (Cattell et al 2022), supporting the notion that strahl scattering by the oblique FM/W instability is not a universal -or even common -process in the inner heliosphere. We note, however, that the required whistler-wave amplitude for effective strahl scattering is small (Jeong et al 2020;Vasko et al 2020) and thus could be hidden in the fluctuation spectrum of the background turbulence in the solar wind (Zank et al 1996;Chen et al 2013;Tong et al 2019).…”
Section: Introductionsupporting
confidence: 56%
“…In addition, in Halekas, J. S. et al (2021) the authors used data provided by the Parker Solar Probe at heliocentric distances between 0.125 and 0.25 AU from the Sun, and concluded that the observed heat-flux dependence on plasma beta is consistent with theoretical thresholds associated with oblique whistler waves generated via the fan instability Vasko et al (2019). In contrast, in Cattell et al (2022), authors showed that whistlers waves are extremely rare inside ∼0.13 AU and the heat-flux vs beta relationship is not constrained by the heat-flux fan instability this close to the Sun.…”
Section: Introductionmentioning
confidence: 72%
“…Different theoretical and observational studies have tried to assess the importance of these HFI on the non-collisional regulation of the electron heat-flux in the solar wind. From the observational point of view, these studies focus on comparing measurements of the normalized electron heat-flux macroscopic moment in the solar wind with analytical expressions of marginal stability thresholds of electron HFI (Gary et al, 1999;Bale et al, 2013;Tong et al, 2019;Halekas, J. S. et al, 2021;Cattell et al, 2022). In Bale et al (2013) the authors contrast data obtained by the WIND spacecraft with theoretical thresholds values for the whistler and magnetosonic instabilities.…”
Section: Introductionmentioning
confidence: 99%